The Effects of Remedies on Merger Activity in Oligopoly - Christian Wey; Markus Dertwinkel-Kalt (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We analyze the effects of structural remedies on merger activity in a Cournot oligopoly when the antitrust agency applies a consumer surplus standard. Remedies increase the scope for profitable and acceptable mergers, while divestitures to an entrant firm are most effective in this regard. Remedial divestitures are most attractive from a social welfare point of view, when the merging parties can extract the entire gains associated with the asset sale. We also show that the merging parties have strong incentives to search for the most efficient buyer and we identify instances so that a remedy rule induces strictly price-decreasing mergers. Finally, under incomplete information an effcient merger type is to be doomed to "overshoot" with its divestiture proposal in a pooling equilibrium which is also possible under separation.
Keywords: L13; L41; K21; 330